2007
DOI: 10.1111/j.1440-172x.2006.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with caring and living conditions in nursing homes: Views of elderly persons, next of kin and staff members

Abstract: The aim was to describe satisfaction with the caring and living conditions of elderly persons in nursing homes, expressed by the elderly persons, next of kin and staff members. Elderly persons were interviewed about their caring and living conditions. Next of kin and staff members completed a questionnaire about satisfaction with caring and living conditions of elderly persons. The main results showed significantly low levels of satisfaction regarding: altered health, influence on care, rehabilitation and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
52
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 10 publications
6
52
0
6
Order By: Relevance
“…Pårørende bidrar til å ivareta beboernes livskvalitet, og det kan se ut som pårørendes involvering også er positivt for kvaliteten på pleien i sykehjemmene (Gaugler, 2005;Grabowski & Mitchell, 2009). Samtidig er det studier som viser at pårørende selv har varierende opplevelser av det å bli pårørende til beboere på sykehjem (Berglund, 2007;Førsund, 2009;Haesler, Bauer & Nay, 2010;Hertzberg, Ekman & Axelsson, 2001). Lav tilfredshet med kontakten med personalet, liten innflytelse på pleien og lite meningsfull aktivisering av beboerne var funn i Berglunds studie (Berglund, 2007).…”
Section: Bakgrunnunclassified
See 1 more Smart Citation
“…Pårørende bidrar til å ivareta beboernes livskvalitet, og det kan se ut som pårørendes involvering også er positivt for kvaliteten på pleien i sykehjemmene (Gaugler, 2005;Grabowski & Mitchell, 2009). Samtidig er det studier som viser at pårørende selv har varierende opplevelser av det å bli pårørende til beboere på sykehjem (Berglund, 2007;Førsund, 2009;Haesler, Bauer & Nay, 2010;Hertzberg, Ekman & Axelsson, 2001). Lav tilfredshet med kontakten med personalet, liten innflytelse på pleien og lite meningsfull aktivisering av beboerne var funn i Berglunds studie (Berglund, 2007).…”
Section: Bakgrunnunclassified
“…Samtidig er det studier som viser at pårørende selv har varierende opplevelser av det å bli pårørende til beboere på sykehjem (Berglund, 2007;Førsund, 2009;Haesler, Bauer & Nay, 2010;Hertzberg, Ekman & Axelsson, 2001). Lav tilfredshet med kontakten med personalet, liten innflytelse på pleien og lite meningsfull aktivisering av beboerne var funn i Berglunds studie (Berglund, 2007). Studier tyder på at flere pårørende ønsker å bidra ved å gi informasjon og sørge for kontinuitet, følge opp kvalitet i pleien og bidra til at hele gruppen beboere får det bedre (Bern-Klug & Forbes-Thompson, 2008;Davies & Nolan, 2006;Rognstad, Sagbakken & Nåden, 2015;Sandberg, Lundh & Nolan, 2001).…”
Section: Bakgrunnunclassified
“…Furthermore, Kajonius and Kazemi (2016d) reported positive effects of two other user-oriented care indicators, namely, treatment and safeness (also used in the present research), in mitigating the effect of loneliness on satisfaction with care. The relationship between interpersonal process quality care indicators and satisfaction with care has been confirmed by a number of empirical studies conducted in different countries and settings (Berglund, 2007;Murphy et al, 2007).…”
mentioning
confidence: 86%
“…It has also been shown that elderly clients place their subjective illness experience at a higher importance as compared to that which is objectively measured (Hagglund, Boman, Lundman, & Brulin, 2008). Thus, it should be noted that there exists good communication between the nursing staff and the elderly client (Berglund, 2007) so as to mold a caring relationship that meets the elderly client's needs and expectations.…”
mentioning
confidence: 93%
“…This view of caring focuses on the human being as a unitary whole, hence, its emphasis on the understanding of human experience as the route through which care can be understood (Parse, 2002). While literature abounds regarding the concept of care concerning areas of nursing practice, nursing administration, and nursing education (Purnell, 2009), an impression reaped from the actual subjective experience of clients is difficult to find (Berglund, 2007).…”
mentioning
confidence: 99%